Factors that affect implementation of a nurse staffing directive: results from a qualitative multi‐case evaluation. (31st March 2016) - Robinson, Claire H.; Annis, Ann M.; Forman, Jane; Krein, Sarah L.; Yankey, Nicholas; Duffy, Sonia A.; Taylor, Beth; Sales, Anne E.
Abstract: Aim/s: To assess implementation of the Veterans Health Administration staffing methodology directive. Background: In 2010 the Veterans Health Administration promulgated a staffing methodology directive for inpatient nursing units to address staffing and budget forecasting. Design: A qualitative multi‐case evaluation approach assessed staffing methodology implementation. Methods: Semi‐structured telephone interviews were conducted from March – June 2014 with Nurse Executives and their teams at 21 facilities. Interviews focused on the budgeting process, implementation experiences, use of data, leadership support, and training. An implementation score was created for each facility using a 4‐point rating scale. The scores were used to select three facilities (low, medium and high implementation) for more detailed case studies. Results/findings: After analysing interview summaries, the evaluation team developed a four domain scoring structure: (1) integration of staffing methodology into budget development; (2) implementation of the Directive elements; (3) engagement of leadership and staff; and (4) use of data to support the staffing methodology process. The high implementation facility had leadership understanding and endorsement of staffing methodology, confidence in and ability to work with data, and integration of staffing methodology results into the budgeting process. The low implementation facility reported poor leadership engagement and little understanding of data sources and interpretation. Conclusion: Implementation varies widely across facilities. Implementing staffing methodology in facilities with complex and changing staffing needs requires substantial commitment at all organizational levels especially for facilities that have traditionally relied on historical levels to budget for staffing.